PEMETAAN ZONASI INDEKS KERENTANAN SEISMIK PADA DAERAH PASCA TAMBANG DI PT.BUKIT ASAM (PERSERO) TBK. UNIT PENAMBANGAN OMBILIN, SAWAHLUNTO - Doli Ali Fitri; Adree Octova; Yoszi Mingsi Anaperta (Journals Mining Engineering : Bina Tambang, 2018)
The microtremor survey and research was conducted on December 10, 2017 in Tanah Hitam and Kandi, Sawahlunto. The aim of this study was to determine the value of seismic vunerability index and its microzonation at ex-mining land PT.BA UPO. The area of this study was in Tanah Hitam and Kandi by taking the microtremor data of 15 locations. The microtremor data were then processed using Horizontal to Vertical Spectral Ratio (HVSR) method to get H/V curve which generates dominant frequency (f0) value and amplification factor (A) at every observation point, which will be used in the seismic vulnerability index calculation (Kg). Seismic vulnerability index microzonation was generated using Surfer11 software. The results showed that the value of seismic vulnerability index in the ex-mining land area is between -5 x 10-6 s2/cm - 75 x 10-6 s2/cm which is categorized as low to high. The low results of seismic vulnerability index (Kg) microzonation located in the Kandi part of ex-mining land area was indicated by values between PND 4 is between 0 x 10-6 s2/cm - 5 x 10-6 s2/cm. The medium results of seismic vulnerability index (Kg) microzonation value indicated by the value of 4 x 10-6 s2/cm sampai 10 x 10-6 s2/cm was indicated by values between 2 x 10-6 s2/cm - 10 x 10-6 s2/cm spread over PND 1 point, PND 10, PND 11, PND 12 and PND 15. For microzonation results high seismic susceptibility index is damaged at point PND 3, PND 5, PND 6, PND 7, PND 8, PND 9, PND 13 and PND 14 with values ranging from 10 x 10-6 s2/cm to 34 x 10-6 s2/cm. And the result of microzonation index of high seismic susceptibility with value of 40 x 10-6 s2/cm to 48 x 10-6 s2/cm at point PND 2 and PND 8. Based on the value of the shear wave velocity (Vs30) the area has a very dense soil and soft rock with a very dense sand or clay end, gravel, at a thickness of several tens of meters. Material composers of alluvial rock formed from delta sedimentation, top soil, mud, etc.Keywords: Ex-Mining of PT.BA UPO, Horizontal to Vertical Spectral Ratio, Microtremor, Seismic Vulnerability Index